MENTORING IN THE FIELDS OF PHYSIOTHERAPY AND INTEGRATED CARE - Gergana Nenova; Paraskeva Mancheva; Todorka Kostadinova; Kalin Mihov; Svetoslav Dobrilov (Peytchinski Publishing, 2018)
creativecommons Index Copernicus Value: 2016 -90,65 SJIF (Scientific Journal Impact Factor): 2017 - 7,61 Global Impact Factor: 2015 - 0,787 JIFACTOR: 2015 - 0,5 back to 2018Jan-Mar;24(1) Journal of IMAB - Annual Proceeding (Scientific Papers) Publisher: Peytchinski Publishing ISSN: 1312-773X (Online) Issue: 2018, vol. 24, issue1 Subject Area: Medicine - DOI: 10.5272/jimab.2018241.1923 Published online: 07 March 2018 Original article J of IMAB. 2018 Jan-Mar;24(1):1923-1927 MENTORING IN THE FIELDS OF PHYSIOTHERAPY AND INTEGRATED CARE Gergana Nenova1ORCID logo Corresponding Autoremail, Paraskeva Mancheva1ORCID logo, Todorka Kostadinova2, Kalin Mihov3ORCID logo, Svetoslav Dobrilov3ORCID logo, 1) Training and research sector of Rehabilitation, Medical College - Varna, Medical University of Varna, Bulgaria. 2) Department of Health Economics and Management, Faculty of Public Health, Medical University of Varna, Bulgaria. 3) Department of Orthopedics and Traumatology, Medical University of Varna, Bulgaria. ABSTRACT: A survey on the opinion of students studying Rehabilitation as a major subject on the role of their mentors and their qualities in the "Student Practice project." The aim of the study is to investigate the point of view of the students, involved in the "Student Practice" project, about the role and the qualities that mentors and academic coaches (physiotherapists) should possess in order to be created a selection criteria. Subject of the survey are 14 students studying at the Medical College of MU-Varna which study "Rehabilitation". These students participated in the "Students practice" project for the period November 2016 - March 2017. A feedback was sought from them through a questionnaire method with an exclusively prepared for the survey questionnaire. The results of the feedback from trainees showed their increased confidence in dealing with patients and their better integration within the work team. The knowledge and skills acquired by students in the "Student practices" project are a prerequisite for the development of mentoring as a priority for the state's education policy, with clear indications for choosing the most appropriate mentor and setting clear tasks for the acquisition of specific knowledge.